Cervical spondylotic myelopathy with occult foramen magnum meningioma--a case for MRI?. Issue 815 (September 1993) - Chakravarty, K.; Scott, D. G.; Dick, D.; Visick, J.
Abstract : A fatal case of occult foramen magnum meningioma is described which presented with features of cervical myelopathy confirmed by cervical myelogram. Surgical decompression led to initial improvement followed by progressive deterioration and death. Postmortem examination revealed a 4 cm diameter foramen magnum meningioma. The dangers of using only standard radiographic investigations of the cervical cord are discussed.